Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Polycyclic aromatic hydrocarbons-enriched diesel exhaust particles induced hypertrophy in rat primary neonatal cardiomyocytes and apoptotic cell death in H9c2 cardiomyocytes - Ching-Chia Wang; Huei-Ping Tzeng; Mei-Chi Hsieh; Kuo-Cheng Lan; Shing-Hwa Liu (Toxicology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Gastrointestinal stability and DPP-IV inhibitory activity of tilapia (Oreochromis niloticus) viscera hydrolysate-derived novel peptides LPCL and TPFLPDE, with LPCL-modulated GLP-1 and PepT1 expression in STC-1 cells - Rhessa Grace Guanga Ortizo; Ching-Shu Lai; Choirul Anwar; Vishal Sharma; Pei-Pei Sun; Chiu-Wen Chen; Cheng-Di Dong; Mei-Ling Tsai (Food Research International, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Hepatoprotective effect of MUFA-enriched refined Greenland halibut fin oil to inhibit hepatic fibrosis in carbon tetrachloride-induced mice - Pei-Pei Sun; Yi-Sheng Tseng; Chien-Chia Chen; Ching-Shu Lai; Cheng-Di Dong; Vishal Sharma; Mei-Ling Tsai (Food Bioscience, 2024)

Predicting survival after radiosurgery in patients with lung cancer brain metastases using deep learning of radiomics and EGFR status - Chien-Yi Liao; Cheng-Chia Lee; Huai-Che Yang; Ching-Jen Chen; Wen-Yuh Chung; Hsiu-Mei Wu; Wan-Yuo Guo; Ren-Shyan Liu; Chia-Feng Lu (Physical and Engineering Sciences in Medicine, 2023)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Seasonal and diurnal variations of greenhouse gas emissions from a saline mangrove constructed wetland by using an in situ continuous GHG monitoring system - Cheng-Pin Tsai; Ching-Mei Huang; Chung-Shin Yuan; Lei Yang (Environmental Science and Pollution Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Identification of 3-MCPD esters to verify the adulteration of extra virgin olive oil - Wei-Ching Hung; Guan-Jhih Peng; Wen-Ju Tsai; Mei-Hua Chang; Chia-Ding Liao; Su-Hsiang Tseng; Ya-Min Kao; Der-Yuan Wang; Hwei-Fang Cheng (Food Additives & Contaminants Part B-Surveillance, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

Effect of metal binding and posttranslational lysine carboxylation on the activity of recombinant hydantoinase - Cheng-Yang Huang; Ching-Chen Hsu; Mei-Chun Chen; Yuh-Shyong Yang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Single Strand DNA Breaks in Human Lymphocytes Exposed to para-Phenylenediamine and its Derivatives - Soi Mei Chye; You Cheng Hseu; Shih-Hsiung Liang; Chin-Hui Chen; Ssu Ching Chen (Bulletin of Environmental Contamination and Toxicology, 2008)

Production of high-content galacto-oligosaccharide by enzyme catalysis and fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Production of High-content Galacto-oligosaccharide by Enzyme Catalysis and Fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)